2018
DOI: 10.1016/j.bbadis.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous osteopontin induces myocardial CCL5 and MMP-2 activation that contributes to inflammation and cardiac remodeling in a mouse model of chronic Chagas heart disease

Abstract: Cardiac dysfunction with progressive inflammation and fibrosis is a hallmark of Chagas disease caused by persistent Trypanosoma cruzi infection. Osteopontin (OPN) is a pro-inflammatory cytokine that orchestrates mechanisms controlling cell recruitment and cardiac architecture. Our main goal was to study the role of endogenous OPN as a modulator of myocardial CCL5 chemokine and MMP-2 metalloproteinase, and its pathological impact in a murine model of Chagas heart disease. Wild-type (WT) and OPN-deficient (spp1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…In aging hearts, osteopontin derived from adipose tissue (and not from the myocardium) was suggested to promote cardiac fibrosis and dysfunction 373 . In a mouse model of Chagas disease, OPN was implicated in cardiac inflammation, fibrosis, and dysfunction 374 . OPN mediated fibrosis in a model of viral myocarditis 375 ; however, in a model of autoimmune myocarditis, osteopontin did not affect inflammation 376 Expression: Upregulated in myocardial infarcts and predominantly localized in activated macrophages 377 , 378 , 379 Role: Protects the infarcted heart from ventricular dilation by promoting collagen deposition 380 i) Stimulation of f fibroblast proliferation through integrin activation 369 , 381 , and protection of fibroblasts from apoptosis 137 .…”
Section: Frangogiannismentioning
confidence: 99%
“…In aging hearts, osteopontin derived from adipose tissue (and not from the myocardium) was suggested to promote cardiac fibrosis and dysfunction 373 . In a mouse model of Chagas disease, OPN was implicated in cardiac inflammation, fibrosis, and dysfunction 374 . OPN mediated fibrosis in a model of viral myocarditis 375 ; however, in a model of autoimmune myocarditis, osteopontin did not affect inflammation 376 Expression: Upregulated in myocardial infarcts and predominantly localized in activated macrophages 377 , 378 , 379 Role: Protects the infarcted heart from ventricular dilation by promoting collagen deposition 380 i) Stimulation of f fibroblast proliferation through integrin activation 369 , 381 , and protection of fibroblasts from apoptosis 137 .…”
Section: Frangogiannismentioning
confidence: 99%
“…[ 2 ]. In Chagas disease, circulating MMP-2 and -9 were proposed as biomarkers for asymptomatic to cardiac form progression [ 5 7 ], and alterations in their activity and expression during T. cruzi acute experimental infection have also been observed [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spp1 is a pro-inflammatory cytokine that orchestrates cell recruitment and cardiac architecture. Caballero et al reported that spp1 − / − mice have a low heart-to-body ratio as well as reduced inflammatory pathology, CCL5 expression, myocyte size, and fibrosis in cardiac tissues, leading to the proposal that endogenous Spp1 is a key player in the pathogenesis of chronic Chagas heart disease [43]. Our observation of Spp1 overexpression in ApoE − / − mouse model indicates that Spp1 may accelerate the process of atherosclerosis by inducing inflammation.…”
Section: Discussionmentioning
confidence: 55%